Desempenho financeiro e esportivo de clubes brasileiros de futebol: efeitos de múltiplas competições e séries - Marotz, Daniela Patrícia (2022)
In the case of football, this sports segment moves large financial amounts, and organizations seek to achieve financial stability simultaneously to a satisfactory performance on the field. It is argued that the financial results of the clubs are influenced by the performance in sports competitions. However, the various competitions and series of the championships remuneratise the clubs in different ways. From this perspective, the research advances in two aspects: 1) the performance in different championships, national and international; 2) the serial changes in the Brazilian Championship. It aims to analyze the relationships between financial and sports performance indicators, considering the effects of multiple competitions and series of Brazilian football clubs. To achieve this, a descriptive, quantitative and documentary research was carried out, using data from the accounting statements of the clubs in the period. Variables of: indebtedness, profitability, liquidity, size of the club, total soccer expenses, total score in the Brazilian Championship, championship series, stage reached in the Brazilian Cup and stage of the Copa Libertadores. The hypotheses argue that the financial performance of the clubs is influenced by sports performance (H1), is influenced by participation in multiple championships (H2) and is influenced by the championship series that the club disputes (H3). To test such hypotheses, regression analysis was used, with panel data. It was found, mainly, that serie A clubs with the highest number of points in the Brazilian Championship tend to increase ROA to reduce indebtedness and advance phase in the Brazilian Cup also decreases indebtedness. When the club is playing in serie B, it tends to have lower levels of profitability and liquidity as expected, indicating that clubs perform worse financially than the elite of national football. The following hypotheses are confirmed: H1, where return and indebtedness are influenced by the sports performance of the clubs, taking into account the performance in the Brazilian Championship; H2 for indebtedness and liquidity, which are impacted by participation in multiple championships; and H3 where ROA and LC are negatively associated with the championship series that the club disputes, that is, they present better indicators of financial performance for the clubs of the Series A. The recommendations would be to evaluate the financial situation when deciding which championships will be played and, mainly, which will be prioritized. In general, Serie A clubs have better financial results, and in some cases, the results showed evidence of worsening in financial indicators when the club participates in other competitions, for example, when the club participates in serie B and Copa do Brasil, simultaneously reducing the rate of return. In this sense, the findings contribute to the managers of football clubs and the work contributes to the discussions about the finances of Brazilian football, effects of playing series A or B and other competitions, proposes performance variables not used in previous studies and presents reflections to clubs.